SWOT Analysis in Increasing the Competitiveness of Local Fashion Products in the Digital Era at XYZ Company - Setiyowati, Anggi (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The SWOT analysis method is employed to pinpoint a company's strengths, weaknesses, opportunities, and threats that affect its overall success. The data related to opportunities and threats is gathered from various channels. Many organizations utilize monitoring services to gather information and assess trends. SWOT analysis examines both external elements and internal factors, which are documented in the IFAS and EFAS matrices. Maintaining competitiveness is vital for ongoing business operations, particularly in fiercely competitive local markets. Aspects like product quality, operational efficiency, innovation, and leadership play a significant role in determining competitiveness. Local businesses must implement effective management strategies. Additionally, a strong online marketing strategy is essential for sustaining revenue, even though some entrepreneurs might face challenges in developing effective plans. The growth of the domestic fashion industry in Indonesia is driving brands to adapt to new trends. This article discusses ways to improve the competitiveness of local fashion products, highlighting the factors that affect competitiveness, the role of innovation, and how businesses in the area adjust accordingly. An examination of company XYZ reveals both its strengths and weaknesses, along with available opportunities and threats. The optimal approach emphasizes using strengths to take advantage of opportunities while innovating in product development.